A review on ferrofluids with the effect of MHD and entropy generation due to convective heat transfer - Devi, N. R.; Moolya, Shivananda; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Padmanathan, P.; Satheesh, A. (Springer Heidelberg, 2022)
The successes of miniaturized electronic components are depending on the effective methods used to transfer the heat developed during its working environments. Suspension of nanoparticles in a base fluid is one such method used to control heat generation. Mixing of an optimal percentage of nanoparticles such as Cu, Ag, Al2O3, TiO2, SiC, Fe3O4, and CNT with base fluids is called nanofluids. Ferrofluids are the topic of interest because of the unavailability of naturally accessible magnetic liquids. Augmentation in the thermophysical property of the ferrofluid by considering the known volume with the base fluid made the researcher work on this topic. Recent applications of ferrofluid in the areas like biomedical, microelectromechanical systems (MEMS), nanoelectromechanical systems (NEMS), heat transfer agents, and dampers increase the interest of scientists. Another method of refining the thermal performance of the system is using a porous medium. The study of the generation of entropy and heat and mass transfer enhancement using nanoparticle and porous media is a new area of research nowadays. The use of nanofluid along with the magnetic field finds maximum application in medicine, MEMS, heat exchanges, lubrication, and solar collectors. A comprehensive review of the earlier research has been made by considering the MHD effect on entropy generation and heat and mass transfer studies with ferrofluid flows are presented in this paper. Also, the cavity of different shapes, different heating positions, and blocks inside the cavities are summarized in this review study.
Keywords: Lid-Driven Cavity; Nonuniform Magnetic-Field; Cu-Water Nanofluid; Laminar Mixed Convection; Natural-Convection; Transfer Enhancement; Forced-Convection; Square Cavity; Al2O3-Water Nanofluid; Shaped Enclosure